2015
DOI: 10.1007/s10608-015-9728-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Positive and Clinical Psychology: Viewing Human Functioning as Continua from Positive to Negative Can Benefit Clinical Assessment, Interventions and Understandings of Resilience

Abstract: In this review we argue in favour of further integration between the disciplines of positive and clinical psychology. We argue that most of the constructs studied by both positive and clinical psychology exist on continua ranging from positive to negative (e.g., gratitude to ingratitude, anxiety to calmness) and so it is meaningless to speak of one or other field studying the "positive" or the "negative". However, we highlight historical and cultural factors which have led positive and clinical psychologies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 114 publications
5
74
0
3
Order By: Relevance
“…Given that well‐being exists on a spectrum from low to high well‐being (Johnson & Wood ), it could be expected that interventions which reduce burnout will also offer positive benefits. This is supported by studies suggesting lower burnout is associated with variables such as higher job satisfaction (Baruch‐Feldman et al .…”
Section: Relevance For Clinical Practicementioning
confidence: 99%
“…Given that well‐being exists on a spectrum from low to high well‐being (Johnson & Wood ), it could be expected that interventions which reduce burnout will also offer positive benefits. This is supported by studies suggesting lower burnout is associated with variables such as higher job satisfaction (Baruch‐Feldman et al .…”
Section: Relevance For Clinical Practicementioning
confidence: 99%
“…For example, cognitive models of suicide have emphasised the role of situation appraisals, suggesting that suicidal thoughts occur when individuals appraise their circumstances in terms of failure (termed 'defeat') and entrapment (Johnson, Gooding, & Tarrier, 2008a;Williams, 1997). Yet such models have been criticised for their acceptance of an overly negative, disorder-based approach to understanding mental health (Johnson & Wood, 2016). By focusing on the development of mental health problems rather than mental wellbeing, it has been suggested that such approaches fail to identify and capitalise on natural coping mechanisms (Johnson & Wood, 2016).…”
Section: Impact Of Failure Experiencesmentioning
confidence: 99%
“…We value Fava and Guidi's provocative contribution to furthering a psychiatry that includes positive well‐being, and we have made similar calls ourselves within clinical psychology to which any criticism would equally apply. We are heartened to see the publication of these radical ideas in a mainstream psychiatry journal and encouraged by the appearance of their paper as the target article to be printed alongside commentaries.…”
mentioning
confidence: 89%